The Small GTPase Rab5c Exerts Bi-Function in Singapore Grouper Iridovirus Infections and Cellular Responses in the Grouper, Epinephelus coioides - Wang, Liqun; Li, Chen; Zhang, Xinyue; Yang, Min; Wei, Shina; Huang, Youhua; Qin, Qiwei; Wang, Shaowen (Frontiers in Immunology, 2020)
The small GTPase Rab5 is one of the master regulators of vesicular trafficking that participates in early stages of the endocytic pathway, such as endocytosis and endosome maturation. Three Rab5 isoforms (a, b, and c) share high sequence identity, and exhibit complex functions. However, the role of Rab5c in virus infection and cellular immune responses remains poorly understood. In this study, based on the established virus-cell infection model, Singapore grouper iridovirus (SGIV)-infected grouper spleen (GS) cells, we investigated the role of Rab5c in virus infection and host immune responses. Rab5c was cloned from the orange-spotted grouper, Epinephelus coioides, and termed EcRab5c. EcRab5c encoded a 220-amino-acid polypeptide, showing 99% and 91% identity to Anabas testudineus and Homo sapiens, respectively. Confocal imaging showed that EcRab5c localized as punctate structures in the cytoplasm. However, a constitutively active (CA) EcRab5c mutant led to enlarged vesicles, while a dominant negative (DN) EcRab5c mutant reduced vesicle structures. EcRab5c expression levels were significantly increased after SGIV infection. EcRab5c knockdown, or CA/DN EcRab5c overexpression significantly inhibited SGIV infection. Using single-particle imaging analysis, we further observed that EcRab5c disruption impaired crucial events at the early stage of SGIV infection, including virus binding, entry, and transport from early to late endosomes, at the single virus level. Furthermore, it is the first time to investigate that EcRab5c is required in autophagy. Equally, EcRab5c positively regulated interferon-related factors and pro-inflammatory cytokines. In summary, these data showed that EcRab5c exerted a bi-functional role on iridovirus infection and host immunity in fish, which furthers our understanding of virus and host immune interactions.